Limestone increased coffee yield and profitability more than phosphogypsum or their combination - Parecido, Renan J. [UNESP]; Soratto, Rogério P. [UNESP]; Perdoná, Marcos J.; Guidorizzi, Fernando V. C. [UNESP]; Gomes, Guilherme G. [UNESP]; Paula, Rodrigo A. [UNESP]; Gitari, Harun I. (Wiley, 2021)
Soil acidity and low concentrations of exchangeable Ca and Mg are among the main factors that limit the Arabica coffee (Coffea arabica L.) yield in Brazil. Constant fertilizations, especially with ammonium-based N, contribute to acidification in the soil region where they are applied. Coffee producers wonder if limestone and phosphogypsum, isolated or combined, can increase coffee yields. A field experiment was conducted from 2015 to 2020 in southeastern Brazil to evaluate the effect of sole application of limestone and phosphogypsum, or their combined application to young coffee trees (2-yr old), on plant nutrition, yield, and profitability of Arabica coffee crop. Treatments included three limestone rates (0, 2,100, and 4,200 kg ha−1), two phosphogypsum rates (0 and 2,300 kg ha−1), and their combinations, which were band applied under coffee plant canopy. Limestone, in association with phophogypsum or when sole-applied, increased the pH and the concentration of Ca and Mg in the soil, whereas the application of phosphogypsum increased Ca and SO4–S concentration. Coffee yields were increased by the sole application of limestone and phosphogypsum (to a lesser extent), but not when they were combined. The most successful treatment was the sole application of limestone, with increases of up to 44% (613 kg ha−1 yr−1 on average) in yield and 43% in economic returns.